การออกแบบและพัฒนากลไก 3 องศาอิศระ สำหรับเครื่องจำลองการเคลื่อนที่แบบกระทัดรัด - เด่น จันทร์ทองอ่อน (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This thesis presents the design of driving simulator for realistic driving feeling. Several simulators are reviewed to study mechanisms and configurations as well as advantage/disadvantage of each model. In order to understand human feeling under motion, we study human perception and use these factors for our design. In additions, we confirm range of motions by performing an experiment to measure key accelerations from a real car in a racing circuit. From overall study, a three DOF simulator is appropriated and can perform realistic motions of vehicle provided that the center of rotation is fixed around the human head. There are several three DOF mechanisms. However, the main mechanism relies on a mechanism called CMS Joint (Concentric Multilink Spherical Joint) because it has three DOF motions with wide range of motion, and can easily control its center of rotation. The simulator uses gravity to simulate vehicle accelerations in forward and transverse directions by tilting human body. The vertical acceleration can generate directly by vertical movement. Finally, a scaling prototype is developed to test motion and control of vehicle simulation.